Effect of the balance between Co(II) and Co(0) oxidation states on the catalytic activity of cobalt catalysts for Ethanol Steam Reforming - Passos, Aline R. [UNESP]; Martins, Leandro [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, Valerie (Elsevier B.V., 2014)
Changes of the oxidation state of cobalt species during activation under H-2 gas and ethanol steam reforming reaction on Co/Al2O3 were investigated using time-resolved operando Quick-XAS analysis. Prior to activation and reaction, the catalysts were calcined at two different temperatures: 450 and 600 degrees C, the cobalt species of the as-calcined catalysts are slightly different depending on the temperature of calcination. At the end of activation the same amount of metallic cobalt (similar to 63%) was detected for both catalysts calcined at different temperatures. The cobalt species interacted more strongly with the support in the catalyst calcined at 600 degrees C, what resulted in the formation of more cobalt aluminate species and lower amount of Co2+. A relationship between the catalytic performance of catalyst and the molar ratio of Co2+/Co-0 was established: deactivation of catalysts mainly occurred by carbon deposition, however the control of Co-2+/Co-0 ratio helped to equilibrate the steps of ethanol activation and carbon oxidation, resulting in stable catalysts. The catalysts calcined at 450 degrees C were more stable and exhibited higher hydrogen selectivity. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cobalt-supported catalyst; Quick-XAS; Ethanol steam reforming